2017
DOI: 10.1539/joh.17-0202-ra
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for personal exposure monitoring of chemicals: Part I

Abstract: This

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…There were also 19 (22%) workers out of the 86 whose indium concentrations exceeded the AL, suggesting that certain provisions must be initiated at their workplaces, such as consecutive exposure measurements, training of employees, and medical surveillance, according to the NIOSH Occupational Exposure Sampling Strategy Manual 9 ) . It has been reported that the condition TLV<X 95 can be used as a definition of “control measures required” 9 , 10 , 11 ) . By this definition, eight of the eleven indium plants required control measures, while the other 3 plants were evaluated as not requiring control measures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were also 19 (22%) workers out of the 86 whose indium concentrations exceeded the AL, suggesting that certain provisions must be initiated at their workplaces, such as consecutive exposure measurements, training of employees, and medical surveillance, according to the NIOSH Occupational Exposure Sampling Strategy Manual 9 ) . It has been reported that the condition TLV<X 95 can be used as a definition of “control measures required” 9 , 10 , 11 ) . By this definition, eight of the eleven indium plants required control measures, while the other 3 plants were evaluated as not requiring control measures.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to conventional statistical analyses, the upper 95th percentile of the log-normal distribution (X 95 ) was calculated using to the following equation: log(X 95 ) = log(GM) + 1.65 × log(GSD), where GM and GSD are the geometric mean and geometric standard deviation, respectively. The condition “TLV<X 95 ” was used to define “control measures required” in the workplace, an unacceptable exposure in accordance with the concept of exposure risk defined by the NIOSH Occupational Exposure Sampling Strategy Manual 9 ) , Bullock and Ignacio 10 ) , and Hashimoto et al 11 ) . We also compared the indium concentrations of individual workers with the Action Level (AL) 9 ) , which is defined by NIOSH as one-half of the REL (0.05 mg In/m 3 ).…”
Section: Methodsmentioning
confidence: 99%
“…Because personal exposure monitoring permits for continuous monitoring of workers' breathing area, it is more simple to follow worker movement and job variety. Depending on the risk and the situation, a reasonable risk evaluation and management can be conducted with flexibility, to establish whether or not to monitor, which monitoring method is required, and the time interval needed before re-monitoring (Hashimoto et al, 2017). The procedure and the concept are very different for area sampling.…”
Section: Personal V/s Area Samplingmentioning
confidence: 99%
“…When conducting personal exposure measurements, it is necessary to record actions and observations [3]. However, recording actions and observations accurately while conducting measurements is difficult because it requires a dedicated observer.…”
Section: Introductionmentioning
confidence: 99%